MENUMBUHKAN MENUMBUHKAN MOTIVASI BERBAHASA ARAB DI KALANGAN SISWI ASRAMA - Siti Mashlahah Al Fikri (Konsorsium Dosen Institut Agama Islam Al-Yasini Pasuruan, 2024)
Arabic plays a crucial role in Islamic education because it is the primary language for understanding the Qur’an and Hadith. Arabic proficiency is not only an academic requirement but also an essential means of internalizing Islamic teachings and values. However, conditions in the female dormitory of MAN Pasuruan City show that many students have limited motivation to actively use Arabic in daily communication, despite recognizing its importance for religious learning. This condition highlights the need for Arabic language development strategies beyond formal classroom instruction that are integrated into students’ daily activities in the dormitory. Accordingly, this study aims to describe effective strategies for fostering Arabic language motivation among female dormitory students. This research employs a qualitative descriptive approach with a case study design. Data were collected through in depth interviews, participatory observation, and documentation to obtain a comprehensive understanding of program implementation and outcomes. The findings indicate that strategies such as daily Arabic conversations (hiwar yaumi), peer tutoring, Arabic language corners, reward based motivation systems, and the integration of Islamic values into language activities significantly increased students’ motivation. Within one month, motivation levels rose from approximately sixty percent to seventy five percent. These strategies created a learning atmosphere, strengthened students’ confidence, and encouraged the development of an Arabic speaking culture in the dormitory. The study offers contributions for Islamic education.